Busca de informações online sobre paciente : relação terapêutica, estilo pessoal do terapeuta e fatores associados - Mazzali, Daniel Bratta (2017)
Introduction: Several changes have been observed in the world due to the increasing presence of the Internet in people's lives and increasingly easier access to the devices needed for its use. In Brazil, the proportion of those who have access to the world-wide web and the Information and Communication Technologies (ICTs) that make it viable is still lower than in most countries of the Northern Hemisphere, but more than half the population, in our country, already has this service available in its daily life. In recent years, studies have been conducted to evaluate and compare traditional models with the viability and effectiveness of Psychology services and services through digital media. However, ICTs also invaded the traditional psychotherapeutic space. Currently both therapist and patient are connected, they are active figures that influence and are influenced within this context of transition in the ways of relating to and accessing information. The clinician himself/ herself, the unique way in which he / she develops and puts himself / herself in their sessions, or their Therapist’s Personal Style (PST), are moderating variables of the therapeutic process and strongly influence its outcome. Thus, these variables can also influence the posture and the perception of the professionals in front of the changes that digitality has been providing within Psychology. A still unexplored and discussed reality of the intersection of ICTs and the practice of psychotherapy is the possibility for psychologists to seek information about their patients on digital media, such as the social network Facebook, or search engines such as Google. This topic of the search for information about patients on the Internet has gained, in recent years, greater attention of researchers, mainly North Americans. The discussions explored the frequency with which these practices occurred, the possible ethical implications involved and the possible repercussions of the possession of this information in the setting and in the relation of the professionals with their attended ones. However, the great majority of studies that address the subject of the Internet within Psychology refers to the effectiveness of online treatments, and even with the existence of such studies, the researchers' positioning still shows uncertainty and they ponder the need for more debates and more specific and up-to-date guidelines. In addition, a significant gap, mainly within the national setting, has been observed in publications in psychology regarding ethical guidelines for therapists in social networks. Goal: To describe the frequency with which the use of the Internet occurs as a source of information about patients and the influences perceived by psychotherapists in their treatments. In addition, it was sought to investigate associations between the positions adopted by the clinicians, the theoretical line and the PTS. Method: Cross-sectional and mixed design research using a semi-structured interview, online patient information questionnaire, and the Therapist’s Personal Style Questionnaire (PST-Q). In the quantitative stage, 108 clinical psychologists participated, 13 men (12.04%) and 95 women (87.96%), whose ages ranged from 23 to 65 years. In the qualitative phase, five clinical psychologists of different theoretical lines with ages between 26 and 58 years were interviewed. Descriptive and inferential statistics were calculated, and qualitative data were submitted to Interpretive Analysis (Erikson, 1986). Results: Most of the interviewees do not perform (69.47%) or have never performed (61.05%) virtual services nor do they have a professional blog or website, but they use at least some ICT to communicate with their patients. A significant portion of the sample (41.05%) alleged that they had intentionally used some virtual tool to find information about their current patients, and an even larger portion (76.84%) claimed to have accidentally encountered information from their patients on the web. The main tools mentioned as means of collecting this information were the Google search engine and the Facebook social media network. Regardless of whether it was accidentally intentional, more than half (63.16%) of those interviewed who found information from their patients on the Internet did not inform patients that they had accessed this information. Most practitioners who came across this type of information did not perceive any influence on the treatment of the patients in question, on their ability to maintain objectivity, or on how comfortable they felt with their patients. Most of the interviewees also did not observe concern to reveal information not brought by their patients in session nor did it report to feel in some way overwhelmed by the information obtained through the Internet. Regarding Therapeutic Relationship (TR), 74.1% of respondents did not notice any effect after discovering information about their patients on the Internet. Over 22.2% observed some improvement in their relationship with patients and 3.7% observed a worsening. When questioned about the ethical aspects, 46.2% indicated that "in no way" they had hurt any limit of the profession, 46.2% judged their actions between not having crossed any limits and having exceeded the professional limits a bit and only 7.7 % of respondents assessed that they had somehow exceeded or disrespected the limits of the role of psychologist. Most subjects (92.63%) continue to seek qualification and are inserted in academic circles. However, the intersection of ICTs and clinical practice was never discussed at any stage of training for most of these professionals (70.45%), nor did they seek specific supervision for this subject (81.03%). There was no significant difference in the professionals' positions regarding their theoretical base line, their age or gender. However, there were significant correlations between the domains of PST and the perception of the unfolding of patients' information discovery via the Internet. Discussion: The postures of professionals in the virtual environments raised suggest ambivalence on the part of psychologists. The presence of ICTs is growing in Brazil and in the world and its reverberations in the personal and professional life of the population can not be ignored (Abreu, Eisenstein, & Estefenon, 2013; IBGE, 2016; Lisboa, Verzoni & Fulginiti, 2017). The observed perceptions suggest ambiguity among the psychologists interviewed. While most of the interviewed professionals use ICT in their professional practice, there is no clarity about the ethical limits of the profession or the current guidelines. The associations found among the PST domains, the perceptions and postures adopted by professionals in the virtual environment, open the way to the design of in-depth training and reflections on the subject. Moreover, according to a systematic review, most of the published articles related to the subject of ICTs and Psychology seem only to address the efficacy and effectiveness of psychological treatments through the web (Hallberg et al., 2015), thus, denoting a lack of studies that problematize and discuss the influences of the virtual tools in the traditional psychotherapeutic setting.